An optimization approach for optimal location & size of DSTATCOM and DG. (15th April 2023) - Ferminus Raj, A.; Gnana Saravanan, A.
Highlights: Decide the optimum location and size of DSTATCOM and DG. Diagnosis the dynamic issues in power system under various environments. DSTATCOM and DG are detected using loss sensitivity factor (LSF). Optimum location is determined by using Dwarf Mongoose Optimization. DMO decide the optimum size of DSTATCOM and DG. Abstract: This manuscript proposes a novel method to decide the optimum location and size of Distribution static compensator (DSTATCOM) and Distribution Generation (DG) are examined. For lessening the loss of power, voltage profile improvement and operation costs of system, the objective function is used under the constraints of equality and inequality. The aim of proposed method is diagnosis the dynamic issues present in the power system under various environments, like healthy conditions and unhealthy conditions. The primary location of both Distribution Generation and Distribution static compensator are detected by using the loss sensitivity factor (LSF). The final optimum location is determined by using Dwarf Mongoose Optimization (DMO) method. The DMO is used to decide the optimum size of Distribution Generation and Distribution static compensator. The aim of the proposed method is an integrated approach of loss sensitivity factor and Dwarf Mongoose Optimization to decide the optimum location and size of Distribution Generation and DSTATCOM for diminishing the loss of power, voltage profile improvement and operation cost. The Distribution Generation and DSTATCOM are simultaneously placed in radial DG. The LSF is used earlier to detect the optimum location of Distribution Generation and Distribution static compensator. The proposed system is performed in MATLAB or Simulink site and the performance of dynamic stability is tested with IEEE standard bench mark systems.